Logatome and Sentence Recognition Related to Acoustic Parameters of Enclosures - KOCIŃSKI, Jedrzej; OZIMEK, Edward (Archives of Acoustics, 2017)
The paper deals with relationship between speech recognition and objective parameters of enclosures.Six enclosures were chosen: a church, an assembly hall of a music school, two courtrooms of different volumes, a typical auditorium and a university concert hall. Dirac 4.1 software was used to record impulse responses (IRs) in the chosen measurement points of each enclosure. On this base, the following objective parameters of the enclosure were determined: Reverberation Time (RT), Early Decay Time (EDT), Weighted Clarity (C50) and Speech Transmission Index (STI). A convolution of the IRs with logatome tests and the Polish Sentence Test (PST) was made. Logatome recognition and speech reception threshold (SRT – i.e., SNR yielding 50% speech recognition) were evaluated and their dependence on the objective parameters were determined. Generally a linear relationship between logatome or SRT and RT or EDT was found. However, speech recognition was nonlinearly related (according to psychometric function) to STI values. The most sensitive range of the logatome and sentence recognition relative to STI changes corresponded to the middle range of STI values. Below and above this range, logatome and sentence recognition were much less dependent of STI changes .